2016
DOI: 10.1371/journal.pone.0154771
|View full text |Cite
|
Sign up to set email alerts
|

Fine-Tuning of Pten Localization and Phosphatase Activity Is Essential for Zebrafish Angiogenesis

Abstract: The lipid- and protein phosphatase PTEN is an essential tumor suppressor that is highly conserved among all higher eukaryotes. As an antagonist of the PI3K/Akt cell survival and proliferation pathway, it exerts its most prominent function at the cell membrane, but (PIP3-independent) functions of nuclear PTEN have been discovered as well. PTEN subcellular localization is tightly controlled by its protein conformation. In the closed conformation, PTEN localizes predominantly to the cytoplasm. Opening up of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 50 publications
(70 reference statements)
1
8
0
Order By: Relevance
“…Therefore, we isolated nuclear protein from the PTEN-WT and PTEN-4A expressing stable cell lines and performed immunofluorescence experiments in 293T cells. We found that PTEN-4A preferentially localized to the nucleus (Figure 2A-C), consistent with recent findings in various cell types [18,[44][45][46][47].…”
Section: Pten-4a Preferentially Localizes To the Nucleussupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, we isolated nuclear protein from the PTEN-WT and PTEN-4A expressing stable cell lines and performed immunofluorescence experiments in 293T cells. We found that PTEN-4A preferentially localized to the nucleus (Figure 2A-C), consistent with recent findings in various cell types [18,[44][45][46][47].…”
Section: Pten-4a Preferentially Localizes To the Nucleussupporting
confidence: 92%
“…Further, several non-genomic mechanisms contribute to PTEN inactivation resulting in oncogenic transformation and progression. PTEN function and subcellular localization is frequently modulated by post-translational modifications, particularly phosphorylation and ubiquitination [16,18,47,61,62]. Indeed, PTEN phosphorylation has increasingly been observed to compromise PTEN function in several cancers [63][64][65][66] and other non-malignant diseases [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…To confirm that Akt activation plays a role in zebrafish neural crest development, we expressed constitutively active human PTEN-mCherry fusion (PTEN S370A, S380A, T382A, T383A, S385A or PTEN QMA) in crestin:EGFP transgenic zebrafish embryos ( Gil et al, 2006 ; Stumpf et al, 2016 ). After sorting embryos based on mCherry fluorescence at 24 hpf, we found that PTEN QMA-mCherry decreases both phospho-Akt and crestin:EGFP expression ( Figure 7A–C ).…”
Section: Resultsmentioning
confidence: 99%
“…pCSDest was a gift from Nathan Lawson (Addgene plasmid # 22423). PTEN QMA-mCherry was from Stumpf et al, 2016 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, angiogenesis and expression of the vascular endothelial growth factor (VEGF) gene were also enhanced in ptena −/− ptenb −/− mutant embryos, and this hypervascularization phenotype was ameliorated by combined treatment with the VEGF receptor inhibitor sunitinib and the PI3K inhibitor LY294002 [ 13 ]. The hypervascularization phenotype was also applied to differentiate the role of the lipid and protein phosphatase activity of PTEN during embryonic development [ 14 ]. Database sequences suggest that medaka also possesses two PTEN genes ( ptena and ptenb ), with ptena being located on chromosome 8 but the chromosomal location of ptenb being unknown.…”
Section: Introductionmentioning
confidence: 99%